Urbanization and development in Asia : multidimensional perspectives - Beall, Jo, 1952-; Guha-Khasnobis, Basudeb; Kanbur, S. M. Ravi.; World Institute for Development Economics Research (New Delhi : Oxford University Press, 2012)
Contributed articles presented at the conference in Kolkata, December 2008.
Includes bibliographical references.
Keywords: Urbanization -- Asia -- Congresses; Rural-urban migration -- Asia -- Congresses